Anomalous component-dependent lattice thermal conductivity in MoWTaTiZr refractory high-entropy alloys - Jian Zhang; Haochun Zhang; Jie Xiong; Shuai Chen; Yong-Wei Zhang; Gang Zhang (iScience)
Summary: Refractory high-entropy alloys (RHEAs) have been of great interest due to their excellent mechanical properties at elevated temperatures. However, there are few studies on their thermodynamic properties. Here, we investigate lattice thermal conductivity of MoWTaTiZr RHEAs using the equilibrium molecular dynamics (EMD) method. First, we consider the finite size effect. Then, the effect of temperature on the lattice thermal conductivity is explored. Remarkably, the lattice thermal conductivity and the reciprocal of the temperature are approximately linearly distributed. Finally, by tuning the elemental concentrations in RHEAs, the influence of each composition on the lattice thermal conductivity is studied. Interestingly, the lattice thermal conductivity decreases after increasing the Ti element. Chemical ordering in RHEAs indicates that Ti-Ti pairs tend to form bonds, and increasing Ti concentration is more likely to form Ti-rich clusters. This research is conducive to understanding the thermal behaviors in RHEAs and promoting the applications of RHEAs.